A Analisa Alat Tanam Padi Dengan Sistem Gerak Putaran: Analysis of Rice Planting Tools with Rotary Motion System - Satrya Wibawa, Made Ardikosa; Anak Agung Gede Pradnyana Diputra; I Wayan Suma Wibawa; I Wayan Marlon Managi; I Nyoman Suparta; I Ketut Suherman (Journal of Applied Mechanical Engineering and Green Technology, 2026)
This study aims to design and develop a circular motion rice planting tool with high efficiency and effectiveness, particularly for narrow rice fields commonly found in Bali. The developed tool features a stainless steel frame, a manual drive system using a rotating spindle, a chain and sprocket transmission system, and a planting mechanism consisting of a main shaft equipped with a mechanical seedling clamp. The tool is ergonomically designed to reduce farmers’ physical workload and simplify maintenance, as it does not require additional energy sources such as fuel or electricity. Performance testing was conducted directly in rice fields located in Subak Ulun Suwi, Gianyar Regency. The testing method compared the time required for rice planting using traditional manual methods and the developed tool. Observation parameters included working time, ease of operation, labor requirements, and consistency of seedling planting results. The results showed that the circular motion rice planting tool significantly improved time efficiency. The average planting time decreased from about 24 minutes per 100 m² using manual methods to approximately 13 minutes per 100 m² using the tool, indicating a time efficiency improvement of nearly 50%. Additionally, the tool reduced farmers’ physical strain because the planting process no longer required prolonged bending. However, some technical challenges were still identified, particularly related to inconsistent numbers of seedlings planted at certain field points. These issues were influenced by variations in mud field conditions, differences in seedling size, and the stability of the clamping mechanism during operation. Overall, the circular motion rice planting tool shows strong potential to improve productivity and planting efficiency, especially in narrow and terraced rice fields. Further development is needed to enhance planting mechanism stability and ensure consistent seedling placement, enabling the tool to become an affordable and practical agricultural mechanization solution suitable for Bali.